Punishment Of The Perpetrator Of Participation (Deelneming) In The Crime Of Maltreatment Of A Child - Aritonang, May Pranita; July Esther; Sihotang, Lesson (Indonesian Journal Publisher, 2025)
Participation (deelneming) is a concept that includes various forms of participation from individuals or groups, both in mental and physical aspects, who are involved in carrying out certain actions that lead to the occurrence of a criminal offense. This study aims to analyze the punishment of perpetrators of participation (deelneming) in the crime of mistreatment of children, with a focus on Decision Number 4/Pid.Sus-Anak/2023/PN Jkt.Sel. The method used is a normative juridical approach, which examines the application of law and the theory of participation in the context of juvenile criminal law. The results showed that AG, as a child involved in the act, had fulfilled the elements of the crime of aggravated maltreatment that was premeditated, although he did not directly commit physical acts. The judge's consideration in handing down the verdict reflected attention to the age of the perpetrator as well as the principle of rehabilitation in the juvenile justice system. The prison sentence of 3 years and 6 months in LPKA reflects efforts to provide a deterrent effect as well as rehabilitation. This research recommends an increased understanding among law enforcers of the theory of inclusion and legal protection for children so that it can be applied fairly and effectively.